RAW MATERIAL REQUIREMENTS PLANNING IN FRUIT JUICE PRODUCTION - Milić, Dušan; Lukač Bulatović, Mirjana; Kalanović Bulatović, Branka; Milovančević, Zoran (Economics of Agriculture, 2016)
The primary purpose of this research is to determine the production capacity requirements of a model fruit juice producer. In addition to fruit processing capacities, the company is in possession of its own land devoted to orchards. The research was conducted on the basis of a balance method, which has been used in fruit production for the planning of processing capacity requirements, i.e. the striking of a harmonious balance between the land capacity utilisation via orchards and the industry of fruit processing. For the planned production of 33,280 tonnes of raw materials, at average yields, the producer should be in possession of an area of 2,344 ha. For the processing capacity of 160 tonnes of raw materials a day, the producer should be in possession of the following diversity and spatial distribution of cultivated fruit species: strawberries (516 ha), raspberries (332 ha), sour cherries (361 ha), apricots (71 ha), peaches (178 ha), blueberries (320 ha), plums (50 hа), pears (89 ha), apples (137 hа), quinces (50 ha), and grapes (240 ha).